Development of Hungary’s Manufacturing Industry in the Conditions of European Integration - Dudin, Mihail Nikolaevich; Frolova, Ð•vgenia Ð•vgenevna; Voykova, Natalia Andreevna; Galkina, Marina Vladimirovna; Vernikov, Vitaly Aleksandrovic (International Journal of Economics and Financial Issues, 2016)
The main historical trends that have formed the background for the transformation ofHungary’s manufacturing industry were considered in this article, and the peculiarities of the development of the industrial sector in the conditions of European integration were studied. The positive and negative aspects of the transformation ofHungary’s manufacturing industry in the conditions of European integration were highlighted in the article. Besides, the basic directions of the further economic and industrial development of the country were formulated. Keywords: European integration, Hungary, countries of Central and Eastern Europe, manufacturing industry. JEL Classifications: F21, L23, O47